Antibacterial activity, corrosion resistance and wear behavior of spark plasma sintered Ta-5Cu alloy for biomedical applications. (October 2017) - Cui, Jing; Zhao, Liang; Zhu, Weiwei; Wang, Bi; Zhao, Cancan; Fang, Liming; Ren, Fuzeng
Abstract: Tantalum has been widely used in orthopedic and dental implants. However, the major barrier to the extended use of such medical devices is the possibility of bacterial adhesion to the implant surface which will cause implant-associated infections. To solve this problem, bulk Ta-5Cu alloy has been fabricated by a combination of mechanical alloying and spark plasma sintering. The effect of the addition of Cu on the hardness, antibacterial activity, cytocompatibility, corrosion resistance and wear performance was systematically investigated. The sintered Ta-5Cu alloy shows enhanced antibacterial activity against E. Coli due to the sustained release of Cu ions. However, the addition of Cu would produce slight cytotoxicity and decrease corrosion resistance of Ta. Furthermore, pin-on-disk wear tests show that Ta-5Cu alloy has a much lower coefficient of friction but a higher wear rate and shows a distinct wear mode from that of Ta upon sliding against stainless steel 440 C. Wear-induced plastic deformation leads to elongation of Ta and Cu grains along the sliding direction and nanolayered structures were observed upon approaching the sliding surface. The presence of hard oxides also shows a profound effect on the plastic flow of the base material and results in localized vortex patterns. The obtained results are expected to provide deep insights into the development of novel Ta-Cu alloy for biomedical applications.